Biochemical markers of contamination in fish toxicity tests - Haluzová, Ivana (Slovak Toxicology Society SETOX, 2011)
Markers of xenobiotic metabolization (cytochrome P450, ethoxyresorufin-O-deethylase, glutathione and glutathione-S-transferase) were investigated in the liver of the common carp Cyprinus carpio after 28-day exposure to different pesticide formulations. The fish exposed to herbicide Sencor 70 WG (metribuzin 700 g/kg) of 0.25 and 2.5 mg/l showed no change in cytochrome P450 and activity of ethoxyresorufin-O-deethylase when compared to control. Successor 600 (pethoxamid 600 g/l) of 0.06; 0.22 and 0.60 mg/l did not affect either cytochrome P450 or the activity of ethoxyresorufin-O-deethylase. However, in fish exposed to Successor 600 of 0.22 and 0.60 mg/l, there was a rise in glutathione and in the activity of glutathione-S-transferase (p<0.05), with Spearman's correlation r = 0.23 at p<0.05. Spartakus (prochloraz 450 g/l) of 0.36 and 1.08 mg/l induced cytochrome P450 and ethoxyresorufin-O-deethylase (p<0.05), with Spearman's correlation r=0.49 at p<0.01. Glutathione increased in fish exposed to 1.08 mg/l (p<0.05), the activity of glutathione-S-transferase rose (p<0.05) in all concentrations tested (0.108; 0.36 and 1.08 mg/l). Spearman's correlation between glutathione and GST was r=0.38; p<0.01). The obtained data contribute to a better understanding of detoxification of the selected xenobitics in fish. Although biomarkers of the first phase of metabolization are considered to be more sensitive, our results indicate higher sensitivity of the second phase biomarkers.